2010
DOI: 10.1038/nature08782
|View full text |Cite|
|
Sign up to set email alerts
|

B-cell-derived lymphotoxin promotes castration-resistant prostate cancer

Abstract: Prostate cancer (CaP) progresses from prostatic intraepithelial neoplasia through locally invasive adenocarcinoma to castration resistant (CR) metastatic carcinoma 1 . Although radical prostatectomy, radiation and androgen ablation are effective therapies for androgen-dependent (AD) CaP, metastatic CR-CaP is a major complication with high mortality 2 . Androgens stimulate growth and survival of prostate epithelium and early CaP. Although most patients initially respond to androgen ablation, many develop CR-CaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
519
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(534 citation statements)
references
References 39 publications
7
519
6
2
Order By: Relevance
“…5 In addition to its cytoplasmic functions where it controls the activation of both classical and alternative NF-κB pathways, 6,[9][10][11][12] IKKα can function as a nuclear protein kinase, [33][34][35] and nuclear IKKα plays important roles in prostate cancer progression and metastasis. 13,14 In the present study we have shown that IKKα controls the biogenesis of a group of miRNA, including miR-196a. Phosphorylation of IKKα at 23 T site promotes the association of IKKα with pri-miRNAs, where MiR-196a has two forms: miR-196a1 and miR-196a2.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…5 In addition to its cytoplasmic functions where it controls the activation of both classical and alternative NF-κB pathways, 6,[9][10][11][12] IKKα can function as a nuclear protein kinase, [33][34][35] and nuclear IKKα plays important roles in prostate cancer progression and metastasis. 13,14 In the present study we have shown that IKKα controls the biogenesis of a group of miRNA, including miR-196a. Phosphorylation of IKKα at 23 T site promotes the association of IKKα with pri-miRNAs, where MiR-196a has two forms: miR-196a1 and miR-196a2.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, we found that IKKα can be translocated into the nucleus and nuclear IKKα plays important roles in prostate cancer progression and metastasis. 13,14 MicroRNAs (miRNAs) regulate gene expression through suppression of translation and decay of target mRNAs, and are involved in diverse physiological and pathological processes. The primary transcripts of miRNA (pri-miRNA) are cleaved into precursor miRNA (pre-miRNA) by nuclear Drosha, and further processed to mature miRNAs by cytoplasmic Dicer1 in mammalian miRNA biogenesis.…”
mentioning
confidence: 99%
“…In a transplanted mammary carcinoma, complement was shown to be involved in myelomonocytic cell recruitment [34], although the mechanisms responsible for complement activation in tumors remain to be defined. It should be noted that B cells can use tools other than antibodies to skew macrophage function and promote tumor progression, including IL-10 and lymphotoxin (LT) [35][36][37][38], and B regulatory cells may be well suited for this [38]. Thus, the mechanisms of co-opting the function of myelomonocytic cells in tumors can differ considerably, although M2-like skewing is a recurrent common denominator.…”
Section: Tam Accumulationmentioning
confidence: 99%
“…A study by Ammirante et al (2010) deals with progression of prostate cancer (CaP), mainly focusing on the mechanisms underlying the recurrence of castration-resistant (CR) metastatic carcinomas. In addition to the previously described TRAMP model, subcutaneous allografts of mouse androgen-dependent AD-CaP cell line myc-CaP, were used to facilitate better mechanistic analysis of CR-CaP development.…”
Section: B-cell-derived Lt Controls Reemergence Of Castrationresistanmentioning
confidence: 99%